An Educational Model for Asynchronous E-Learning. A Case Study in a Higher Technology Education - Papachristos, Dimitris; Alafodimos, Nikolaos; Arvanitis, Konstantinos; Vassilakis, Kostas; Kalogiannakis, Michail; Kikilias, Panagiotis; Zafeiri, Evi (International Journal of Advanced Corporate Learning (iJAC), 2010)
Nowadays, the use of Web based Education (WbE) in distance learning education is considered to be an innovative method of learning. Supportive parties argue that WbE renews the educational practice through the use of computers and their applied methodology, as well as the technologies provided by the use of the internet. These result in consciously renewing the educational material and in creating a flexible structure which promotes the individualization of learning. The proposed model aims at delivering technological classes through the internet, offering a flexible use of means and tools, allowing a synthetic presentation of selected bibliographic texts that cover the whole cognitional object, developing a cooperative spirit and individualising the learning procedure.